Mens rea, wrongdoing and digital advocacy in social media: Exploring quasi-legal narratives during #deleteuber boycott - Illia, Laura; Colleoni, Elanor; Ludovico, Nuccio; Ravindran, Kiron (John Wiley and Sons Ltd, 2022)
#Boycotts represent digital advocacy attempts in which users publicly punish an organization as a lurata (i.e.,jury),which assesses the guilty intent,the mens rea (i.e.,guilty mind),from a set of visible acts,the actus reus (i.e.,wrongdoings). Yet,we know little about the quasi-legal narratives advocated by users. To this aim,we developed a mixed method study of the #deleteuber boycott on Twitter. Our findings suggest that while users advocate both an Uber-specific and a shared mens rea of Uber with sharing economy firms or the tech giants of Silicon Valley,the latter narrative is the most prominent one; its use depends on whether users are part of a lurata of influencers or not. These findings provide a contribution to studies on public affairs that focus on online activism,boycotts in social media and digital advocacy because they increase our understanding of the opaque legal motivations that provoke boycotters. Also,they highlight that social media blurs the boundaries between boycotts directed at the firm from the boycotts arising indirectly due to the shameful acts of the industry or peers.
Keywords: #Boycott; Actus reus; Digital advocacy; Lurata; Mens rea; Sharing economy; Social media; Uber; 63 Sociología::6308 Comunicaciones sociales; ODS 3 - Salud y bienestar